2012
DOI: 10.1200/jco.2012.42.1149
|View full text |Cite
|
Sign up to set email alerts
|

Is Family History Associated With Improved Survival in Patients With Gastric Cancer?

Abstract: We are grateful to Hudis et al 1 for the opportunity to clarify both the limitations and uses of observational data in the assessment of clinical questions. With regard to the benefits of dosedense chemotherapy for elderly patients with hormone-positive breast cancer, we agree that there are subsets of older patients who are hormone positive who benefit from the addition of chemotherapy to hormone therapy, and likely a subset of those who benefit from more intensive therapy and dose-dense therapy. Current stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…By contrast, a large Korean study of 1,273 patients with gastric cancer showed that a first-degree FHX was associated with a reduced risk of recurrence and death in patients with stage III–IV gastric cancer [13]. However, this study is limited by the small number of patients in the stage III–IV group (only 48 cases with a FHX) and the unusually young age of the patients without a FHX [19]. …”
Section: Discussionmentioning
confidence: 98%
“…By contrast, a large Korean study of 1,273 patients with gastric cancer showed that a first-degree FHX was associated with a reduced risk of recurrence and death in patients with stage III–IV gastric cancer [13]. However, this study is limited by the small number of patients in the stage III–IV group (only 48 cases with a FHX) and the unusually young age of the patients without a FHX [19]. …”
Section: Discussionmentioning
confidence: 98%